2003
DOI: 10.1074/jbc.m306444200
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Conserved Motifs in the Hepatitis C Virus NS3 Protein Critical for Helicase Action

Abstract: The hepatitis C virus (HCV) NS3 helicase shares several conserved motifs with other superfamily 2 (SF2) helicases. Besides these sequences, several additional helicase motifs are conserved among the various HCV genotypes and quasispecies. The hepatitis C virus (HCV)1 has caused a global crisis by infecting more than 2% of the world's population (1). Combination therapies using interferon and the antiviral drug ribavirin eliminate HCV in a majority of patients but such treatments are costly and cause debilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 41 publications
(60 reference statements)
6
98
2
Order By: Relevance
“…The Protease Domain Aids RNA Unwinding-Previous studies using Hel-His have shown that it unwinds RNA poorly relative to DNA (15,16), and when excess DNA is added upon initiation to reactions containing Hel-His, virtually no RNA unwinding is detected (15). Although a preference for DNA has been long established for HCV helicase (32), the absence of RNA helicase activity in the presence of an enzyme trap (such as excess DNA) starkly contrasted results published previously by other authors (25,31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Protease Domain Aids RNA Unwinding-Previous studies using Hel-His have shown that it unwinds RNA poorly relative to DNA (15,16), and when excess DNA is added upon initiation to reactions containing Hel-His, virtually no RNA unwinding is detected (15). Although a preference for DNA has been long established for HCV helicase (32), the absence of RNA helicase activity in the presence of an enzyme trap (such as excess DNA) starkly contrasted results published previously by other authors (25,31).…”
Section: Resultsmentioning
confidence: 99%
“…Cloning, expression, and purification of Hel-His (which was previously designated Hel-1a) have been described (15). A detailed enzymatic characterization of Hel-1a was reported recently (16).…”
Section: Protein Expression/purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence of the samples with QR2 subtracted by that of the samples without QR2 is used as the fluorescence of the QR2-polyphenol complex. The obtained values were globally fitted to an exhaustive binding model (25) with the software Prism.…”
Section: Affinity Characterization By Fluorescence Quenchingmentioning
confidence: 99%
“…Dda contains a long -hairpin which is anchored at its tip by electrostatic interactions to domain 2B, allowing it to function not only directly in splitting the dsDNA but also in coupling ATP hydrolysis to unwinding (He et al, in press). Like Dda, the hepatitis C virus NS3 helicase (SF2) contains an extended pin [100], and mutation of conserved residues with this pin also uncouples ATP hydrolysis from unwinding [130].…”
Section: Duplex Dna Is Split By the Pin Regionmentioning
confidence: 99%